Types of social media activities and Hong Kong South and Southeast Asians Youth's Chinese language learning motivation. (April 2021) - Lai, Chun; Tai, Chung-Pui
Abstract: Social media hold great potential for language learning since language learning is closely intertwined with socialization. However, previous studies have primarily examined social media experience as a whole, without taking into consideration of the differential influences of different types of social media activities. This study examined how different social media activities impacted language learning motivation through analyzing survey responses from 565 secondary school south and southeast Asian students in Hong Kong. The structural equation modeling analysis revealed that passive consumption of social media contents and active contribution of social media contents both contributed positively to language learning motivation via both cultural identification and ideal L2 self. However, the two types of social media activities were associated with cultural identification differently, where passive consumption predicted bicultural harmony and active contribution predicted bicultural blendedness. The findings confirm the value of both types of social media activities and suggest capitalizing on the motivational impact of everyday social media activities for language learning. The findings call for in-depth research into the differential impacts of different social media activities.